ANALISIS PENGEMBANGAN WILAYAH KABUPATEN PASAMAN BERBASIS POTENSI UNGGULAN DAERAH - Renaldi Dwi Setiyo Saputro (LPSDI Bina Patria, 2023)
This research reveals about the development of the Pasaman Regency area based on superior potential. The analytical tools used in this study are Location Quotion analysis, Klassen Typology analysis and Shift Share analysis. The results of the study show that there are 3 economic sectors in Pasaman Regency which are the basic (leading) sectors. From the results of the LQ analysis, information was obtained that the base sector with the highest LQ value was the Agriculture, Forestry and Fisheries sector with an LQ value of 2.188 while the base sector with the lowest LQ value (1.046) was the Water Supply sector. From the results of the Klassen Typology analysis it was identified that there were only 2 sectors that were included in the category of developed and fast growing sectors (quadrant I), there was only 1 sector that was included in the growing category (Quadrant II) 5 sectors were included in the category of developed but depressed sectors (Quadrant II) III) and 9 Sectors fall into the category of relatively underdeveloped sectors (Quadrant IV). Meanwhile, from the results of the Shift Share analysis calculation, it is known that the regional growth component (N) is positive and the industrial mix component (M) in the Pasaman area has positive value sectors, namely water supply, waste procurement, waste and recycling, construction, wholesale and retail trade, car and motorcycle repair, accommodation and food and drink provision, information and communication, financial and insurance services, government administration, defense and compulsory social security, educational services, health services and social activities, other than the sectors above are negative while the competitive power component (C) for all sectors is negative except for the agriculture, base and fishery sectors, the transportation and warehousing sector. , the accommodation and food and drink provision sector, the education service sector, the health service sector and social activities, the other service sector